Virtual educational proposal in cardiopulmonary resuscitation for the neonate care - Gonçalves, Gilciane Ribeiro; Peres, Heloisa Helena Ciqueto; Rodrigues, Rita de Cássia; Tronchin, Daisy Maria Rizatto; Pereira, Irene Mari (Revista da Escola de Enfermagem da USP, 2010)
The purpose of this study was to develop an educational proposal using virtual multimedia resources, to innovate, stimulate and diversify areas of communication and interaction, facilitating nurses' autonomous and reflexive process of teaching and learning. This is an applied research, following the cyclical and interactive phases of designing, planning, developing and implementing. The educational proposal was developed on the TelEduc platform, using specific tools for content organization and communication between students and administrator. The teaching modules were on the following themes: Module 1 - Fundamentals of the heart anatomy and physiology in newborns; Module 2 - Risk factors for the occurrence of cardiorespiratory arrest in newborns; Module 3 - Planning nursing care; Module 4 - Medications used in cardiopulmonary arrests in newborns; and Module 5 - Cardiorespiratory arrest care in newborns. This study may contribute to innovating teaching in nursing from a virtual educational proposal on the important issue of newborn cardiopulmonary resuscitation care.